2023
DOI: 10.18203/2349-3259.ijct20230350
|View full text |Cite
|
Sign up to set email alerts
|

Validation of interpretation of ST-elevation myocardial infarction using the smartphone based 12 lead electrocardiograms in comparison to the cardiologist-a cross sectional study, validation study, single-center study

Abstract: Background: In patients experiencing an ST-elevation myocardial infarction (STEMI), rapid diagnosis leads to optimal clinical outcomes. Recent technology has provided access to a reliable means of obtaining an ECG reading through a smartphone application (app) that works with an attachment providing all 12-leads of a standard ECG system. We developed a 12-lead smartphone-based electrocardiogram (ECG) called “Spandan”, and an application to accurately assess the presence of STEMI in patients presenting with che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Haberman et al discovered that in patients in cardiology clinics, the handheld ECG with single lead data acquistion had a sensitivity of 94% and a specificity of 99%. [19] Hospitalized patients had lower readings with a sensitivity range of 55-79% and a specificity range of 97.5-97.9%, according to Spandan smartphone ECG showed that it has specificity and Sensitivity to record the 12 lead ECG for rhythms abnormalities, STEMI, NSTEMIS and Arrhythmias like AF. [20][21][22] Limitations:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haberman et al discovered that in patients in cardiology clinics, the handheld ECG with single lead data acquistion had a sensitivity of 94% and a specificity of 99%. [19] Hospitalized patients had lower readings with a sensitivity range of 55-79% and a specificity range of 97.5-97.9%, according to Spandan smartphone ECG showed that it has specificity and Sensitivity to record the 12 lead ECG for rhythms abnormalities, STEMI, NSTEMIS and Arrhythmias like AF. [20][21][22] Limitations:…”
Section: Resultsmentioning
confidence: 99%
“…[19] Hospitalized patients had lower readings with a sensitivity range of 55-79% and a specificity range of 97.5-97.9%, according to Spandan smartphone ECG showed that it has specificity and Sensitivity to record the 12 lead ECG for rhythms abnormalities, STEMI, NSTEMIS and Arrhythmias like AF. [20][21][22] Limitations:…”
Section: Resultsmentioning
confidence: 99%